Inherited Chromosomally Integrated Human Herpesvirus 6: An Unexpected Finding in a Septic Neonate. Issue 1 (January 2021) - Pugni, Lorenza; Pietrasanta, Carlo; Ronchi, Andrea; Lunghi, Giovanna; Pellegrinelli, Laura; Mosca, Fabio; Campanini, Giulia; Baldanti, Fausto
Abstract : Human herpesvirus 6 (HHV-6) can integrate its genome in human chromosomes and be germline transmitted (inherited chromosomally integrated HHV-6). We report a case of chromosomally integrated HHV-6 inherited from the mother unexpectedly diagnosed in a septic neonate. Since HHV-6 has recently been included in multiplex polymerase chain reaction assays for meningitis/encephalitis, diagnosing inherited chromosomally integrated HHV-6 status is essential to avoid misdiagnosis of active HHV-6 infection and unnecessary antiviral treatment.